Central Precocious Puberty Following Treatment of Precocious Pseudo-Puberty Caused by Leydig Cell Tumor: A Pediatric Case and Literature Review - Jeong Ho Ahn; Ji Kyoung Park; Soo Jin Jung; Jeong Eun Lee (Clinical Pediatric Hematology-Oncology, 2022)
Leydig cell tumors can cause precocious puberty in prepubertal males. Radical orchiectomy is the standard therapy for Leydig cell tumors, with a good overall prognosis. Here, we present a rare case of secondary central precocious puberty caused by a Leydig cell tumor in a 5 year-old boy. He had an isosexual precocity and advanced bone age. Laboratory investigations showed high testosterone and low gonadotropin levels, presenting as precocious pseudo-puberty. Seven months after surgical removal of the tumor, the patient was diagnosed with central precocious puberty by GnRH stimulation test. He was initiated on GnRH agonist therapy, which has been administered every 13 weeks to date. Post-surgery surveillance of Leydig cell tumors should include evaluation for progression to secondary central precocious puberty as well as recurrence of Leydig cell tumor or metachronous tumors in prepubertal children.